Aristotle's metaphysics Lambda : annotated critical edition based upon a systematic investigation of Greek, Latin, Arabic and Hebrew sources - Alexandru, Stefan, 1966- (Philosophia Antiqua, 2013)
In this annotated critical edition of Aristotle's Metaphysics Lambda Stefan Alexandru explores and utilizes for the first time numerous previously neglected textual sources, written in Greek, Latin, Arabic, and Hebrew. The twelfth book of the Metaphysics , originally an independent treatise, is crucial for the understanding of Aristotle's philosophy, primarily because the doctrine of the Unmoved Mover is nowhere else set forth in greater detail. Not only all the forty-two formerly known Greek codices have been collated, but also commentaries and translations. Moreover, a hitherto undiscovered, independent manuscript, representing a tenuous and particularly valuable branch of the direct tradition, is minutely investigated. The document in question, preserved in the Vatican, is an autograph of the Byzantine humanist and Ecumenical Patriarch Gennadios II Scholarios.